Optimization Of The Annealing Temperature With Degenerate Primer For Amplification Of Arginine Decarboxylase (ADC) Fragment Gene From Genomic DNA of Maluku Tenggara Local Cassava - Kurniawati, Siti; Hartati, Sri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Arginine decarboxylase (ADC) is a key enzyme responsible for polyamines biosynthesis and has been shown to increase resistance to biotic and abiotic stress. Cassava (Manihot esculenta Crantz.) is able to grow and produce storage roots well on marginal land. The purpose of this study was to optimize annealing temperature of primers in PCR reaction to amplify candidate cassava ADC gene fragments. Annealing temperature is a crucial factor in PCR reaction affecting product (gene fragments) specificity. Four pairs of primers; MeADC1, MeADC2, MeADC3, andMeADC4, were designed using degenerate method from several plants species such as Jatropa curcas (Acc XM_022220421), Populus trichocarpa (Acc XM_002306105.2), Capsicum annuum cv Nockwang (Acc KC160547.1) and Lycopersicon esculentum (Acc L16582.1). All primer pairs successfully amplified DNA fragments from local cassava genotypes (Maluku Tenggara/Malra) including Malra012 and Malra016. The MeADC1 primer amplified DNA fragment with less than 1,000 base pairs (bp) at annealing temperature of 46°C, 47°C and 48°C. However, analysis of PCR product sequencing results using NCBI BLAST method showed that the amplified DNA fragment encodes for ribosomal protein S3 of Oryza minuta (Acc YP_009242005.1).Keywords: arginine decarboxylase, annealing, ADC, cassava, Maluku Tenggara, PCR